20.8k views
4 votes
Given the differential Equation (dy/dx)+(2/x)y=x^2y^3 ;solve this equation using the Bernoulli method; Final answer should be (1/y^2)=?

User Fosna
by
4.4k points

1 Answer

0 votes

Answer:


(1)/(y^2)=2x^3+Cx^4.

Explanation:

Given differential equation


\frac{\mathrm{d}y}{\mathrm{d}x}+(2)/(x)y=x^2y^3

Differential equation can be write as


y^(-3)\frac{\mathrm{d}y}{\mathrm{d}x}+(2)/(x)y^(-2)=x^2

By Bernoulli method

Susbstitute
y^(-2)=t.....{equationI}

Differentiate equation I w.r.t x then we get


\frac{\mathrm{d}t}{\mathrm{d}x}=-2y^(-3)\frac{\mathrm{d}y}{\mathrm{d}x}


-(1)/(2)\frac{\mathrm{d}t}{\mathrm{d}x}=y^(-3)\frac{\mathrm{d}y}{\mathrm{d}x}

Susbstitute the values in the given differential equation then we get


-(1)/(2)\frac{\mathrm{d}t}{\mathrm{d}x}+(2)/(x)t=x^2


\frac{\mathrm{d}t}{\mathrm{d}x}-(4)/(x)t=-2x^2

It is first order linear differential equation and compare with the first order linear differential equation
\frac{\mathrm{d}y}{\mathrm{d}x}+P(x)y=Q(x)

Then we get P(x)=
-(4)/(x) and Q(x)=
-2x^2

Integration factor=
e^\intP(x)dx

Integration factor=
e^{-\int(4)/(x)dx

Integration factor=
e^(-4lnx)=e^{lnx^(-4)}=x^(-4).

Using
e^(logb)=b


t* (1)/(x^4)=\int{-2x^2}*(1)/(x^4)dx+C


t=-2x^4{\intx^(-2)dx+C}


t=2x^4*(1)/(x)+Cx^4


t=2x^3+Cx^4

Substitute
t=(1)/(y^2) then we get


(1)/(y^2)=2x^3+Cx^4.

Answer:
(1)/(y^2)=2x^3+Cx^4.

User Yene Mulatu
by
4.7k points